2013
DOI: 10.1111/ajps.12026
|View full text |Cite
|
Sign up to set email alerts
|

When Payouts Pay Off: Conditional Cash Transfers and Voting Behavior in Brazil 2002–10

Abstract: EmpresasThis article estimates the electoral effects of conditional cash transfers (CCTs) in three presidential elections in Brazil. It analyzes municipal-level electoral results and survey data and employs matching techniques to reduce causal inference problems typical of observational studies. Results show that CCTs are associated with increased performance by the incumbent party presidential candidate in all three elections but that these effects have been reaped by incumbents from different parties. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(164 citation statements)
references
References 32 publications
7
136
1
8
Order By: Relevance
“…In line with recent contributions in the economic voting literature (e.g. Pop-Eleches and Pop-Eleches 2012;Zucco 2013;Tilley et al 2018), we have demonstrated that pocketbook assessments affect how citizens make sense of government performance. Results also contribute to debates of how private safety nets affect governance in illiberal democracies.…”
Section: Resultssupporting
confidence: 88%
“…In line with recent contributions in the economic voting literature (e.g. Pop-Eleches and Pop-Eleches 2012;Zucco 2013;Tilley et al 2018), we have demonstrated that pocketbook assessments affect how citizens make sense of government performance. Results also contribute to debates of how private safety nets affect governance in illiberal democracies.…”
Section: Resultssupporting
confidence: 88%
“…A series of studies suggest that personal economic circumstances have a significant effect on electoral behaviour. Voters respond to specific policies with direct consequences for their own welfare, such as disaster relief or cuts in social expenditure, by adjusting their political preferences and vote choices (Bechtel and Hainmueller 2011;Malhotra 2010, 2013;Margalit 2012;Zucco Jr 2013). Likewise, economic self-interest is found to be a key determinant of welfare preferences, with income, employment risk and social protection being strong predictors of attitudes towards redistribution (Rehm 2011;Hacker et al 2013).…”
Section: The Crisis and The Eurosceptic Votementioning
confidence: 99%
“…When it comes to political effects, existing studies have focused on turnout and electoral preferences (e.g., De La O 2013;Zucco 2013). State-society relations have been neglected, despite good reasons to expect CCT programmes to have consequences in this regard by providing benefits to citizens who are mostly neglected by traditional social protection systems.…”
Section: Introductionmentioning
confidence: 99%